Pregnancy and multiple sclerosis: the initial results from a Brazilian database Gravidez e esclerose múltipla: resultados preliminares de base de dados Brasileira - Yara Dadalti Fragoso; Alessandro Finkelsztejn; Elizabeth Regina Comini-Frota; Paulo Diniz da Gama; Ansderson Kuntz Grzesiuk; Jussara Mathias Netto Khouri; Soniza Vieira Alves-Leon; Rogério de Rizo Morales; Marco Aurélio Lana-Peixoto; Cristiane Franklin da Rocha (Arquivos de Neuro-Psiquiatria)
PURPOSE: Pregnancy management poses an extra challenge to physicians and their multiple sclerosis (MS) patients. There are few papers reporting databases on the subject. METHOD: Brazilian database from nine MS clinical and research units, with complete data on 47 pregnant women (49 pregnancies). RESULTS: Despite relatively high exposure to MS medications, no birth defects were reported. Low birth weight and prematurity were similar to those for developing countries. Three complications may have been associated with these medications, while three others were considered to be of purely obstetric nature. CONCLUSION: Our results confirm previous findings on lower relapse rate during pregnancy and add to the present literature informing on data related to drug exposure. PROPÓSITO: O manejo da gravidez cria um desafio extra aos médicos e aos pacientes com esclerose múltipla (EM). Existem poucos trabalhos relatando bases de dados neste tema. MÉTODO: Base de dados brasileira de nove centros clínicos e de pesquisa na EM, com dados completos de 47 mulheres grávidas (49 gestações). RESULTADOS: Apesar da exposição a drogas para EM ter sido relativamente alta, não foram registradas malformações. Baixo peso e prematuridade foram semelhantes àqueles de países em desenvolvimento. Três complicações podem ter sido associadas a drogas, enquanto outras três foram consideradas como sendo de natureza puramente obstétrica. CONCLUSÃO: Nossos resultados confirmam os achados de menor taxa de surtos na gestação e adicionam dados relacionados a exposição a drogas, na literatura atual.